2023
DOI: 10.1007/s11306-023-02019-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and lipidomics studies of parasitic helminths: molecular diversity and identification levels achieved by using different characterisation tools

Abstract: Introduction Helminths are parasitic worms that infect millions of people worldwide and secrete a variety of excretory-secretory products (ESPs), including proteins, peptides, and small molecules. Despite this, there is currently no comprehensive review article on cataloging small molecules from helminths, particularly focusing on the different classes of metabolites (polar and lipid molecules) identified from the ESP and somatic tissue extracts of helminths that were studied in isolation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Metabolic signatures of helminth parasites were actively explored in various studies, however in the context of EVs, data are few and sparsely available (Wangchuk et al., 2023 ; Whitman et al., 2021 ). Interestingly unlike other helminth parasites, EV from T. solium induced anti‐inflammatory gene expression in macrophages and did not show any change in the expression of IL‐1β and TNF‐α (Figure 3a ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic signatures of helminth parasites were actively explored in various studies, however in the context of EVs, data are few and sparsely available (Wangchuk et al., 2023 ; Whitman et al., 2021 ). Interestingly unlike other helminth parasites, EV from T. solium induced anti‐inflammatory gene expression in macrophages and did not show any change in the expression of IL‐1β and TNF‐α (Figure 3a ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted by Wangchuk’s group at James Cook identified the pharmaceutical potential of Australian Wet Tropics plants affected by climate change, and they have also discovered two novel drug lead molecules from one of the ecologically-directed tropical montane cloud forest plants [ 53 , 54 ]. Similarly, potent small molecules anti-inflammatory excretory-secretory products (ESP) derived from parasitic helminths were identified using metabolomics and lipidomics platforms [ 55 , 56 ].…”
Section: Approaches and Techniques For The Biodiscovery Of Anti-infla...mentioning
confidence: 99%